MODEL PENDIDIKAN ISLAM BERBASIS MULTIKULTURAL: Muhamad Ansori, M.Pd.I, IAI Al-Qodiri Jember - Muhamad Ansori (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2018)
This article describe s the discourse of multicultural edu ca- tion, which some experts views as the best suited concept of education for Indonesia. This concept reflects the nature of the Indonesian nation as a multicultural country . But on the other hand, it raises disagreement among communities of Indonesia, known as a muslim majority country , to carry out multi cultural education as that it is not derived from the teachings of Islam. To meet the a descri ption on the development model of multi cultural educational from Islamic theology base, this research is conducted through library research where sources of data were taken from primary and se cundary data sources.